Empirical Studies for the Assessment of the Effectiveness of Design Patterns in Migration between Software Architectures of Embedded Applications. (6th December 2012) - Lakhani, Farah; Pont, Michael J.
Abstract : Two main architectures used to develop software for modern embedded applications are "event triggered" (ET) and "time triggered" (TT). ET designs involve creating systems which handle multiple interrupts; by contrast, only one interrupt is ever enabled in a TT design, and this interrupt is usually linked to a timer "Tick." Although TT architectures are widely used in safety-related designs, they are less familiar to developers of mainstream embedded systems. The work on this research began from the premise that—for a broad class of systems—the use of a TT architecture would improve reliability. The overall goal of the work presented here was to identify ways in which the effort involved in migrating between existing ET architectures and "equivalent" TT architectures could be reduced. The specific goal of the research was to explore whether the use of an appropriate set of design patterns could assist developers who wished to migrate between ET and TT designs. An empirical evaluation of the efficacy of a newly proposed pattern collection is described in this paper. The results of these trials demonstrate that the proposed collection of patterns has the potential to support developers by helping them to take appropriate decisions during the migration process.